Weapon Carrying and Weapon Brandishing at School: Responses to Strain Among Same-Sex Attracted Youth - Teasdale, Brent E. (Journal of interpersonal violence, 2022)
Studies consistently find lesbian, gay, bisexual, and questioning youth are more likely than other youth to experience discrimination, fear for their safety, and be victimized at school. We argue that same-sex attracted youth may be more likely to both carry weapons and to brandish those weapons as coping mechanisms in response to the strain of real or perceived mistreatment school. Using data from the National Longitudinal Study of Adolescent to Adult Health (Wave 1, 1994?1995), we examine the relationships between same-sex attraction, fear, victimization, weapon carrying, and weapon brandishing at school. We find that same-sex attracted youth are significantly more likely than other youth to carry a weapon to school, and to brandish the weapon in front of peers. Consistent with general strain explanations, victimization, discrimination, and fear mediate the association between sexual minority status and both outcomes. We discuss the implications of these patterns for primary prevention interventions.